2021
DOI: 10.1177/00368504211031693
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of non-Newtonian blood flow in an artery having multiple stenosis and electroosmotic effects

Abstract: The electro-osmotically modulated hemodynamic across an artery with multiple stenosis is mathematically evaluated. The non-Newtonian behaviour of blood flow is tackled by utilizing Casson fluid model for this flow problem. The blood flow is confined in such arteries due to the presence of stenosis and this theoretical analysis provides the electro-osmotic effects for blood flow through such arteries. The mathematical equations that govern this flow problem are converted into their dimensionless form by using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…They concluded that by adding gold nanoparticles, the velocity of blood increases and they also compared their results to Cu and TiO 2 models. A number of researchers [7][8][9][10] have paid attention to the study of arterial diseases by applying different methods.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that by adding gold nanoparticles, the velocity of blood increases and they also compared their results to Cu and TiO 2 models. A number of researchers [7][8][9][10] have paid attention to the study of arterial diseases by applying different methods.…”
Section: Introductionmentioning
confidence: 99%
“…The flow of the blood through an artery having multiple stenoses of both symmetric and non-symmetric shapes is studied by Zidan et al [36]. Several theoretical studies were also conducted to discuss the flow motions driven by combined electroosmosis and peristaltic pumping [2,5,6,17,21,22,27].…”
Section: Introductionmentioning
confidence: 99%
“…Further study about the blood flow in an artery having multiple stenoses is done by authors. [37][38][39][40] Literature shows that graphene oxide and titanium dioxide exhibit unique sets of material properties. To the authors' best knowledge, no work is performed to evaluate the impact of resistive and radiative heats on the GO and TiO 2 suspended Sutterby blood flow through the stenosed artery in the existence of the Darcy-Forchheimer, heat convection, and hydromagnetic conditions.…”
Section: Introductionmentioning
confidence: 99%